ENVIRONMENT OF ROOTING AND SUBSTRATUM IN THE MINICUTTING OF ERVA-MATE - BRONDANI, Gilvano Ebling; WENDLING, Ivar; SANTIN, Delmar; BENEDETTI, Eliziane Luiza; ROVEDA, Luís Fernando; ORRUTÉA, Alessandro Góis (Scientia Agraria, 2007)
The inexistence of one method of vegetative propagation for erva-mate of efficient form difficult the silvicultural advances of this species. The experiment was carried in the Embrapa Florestas, with the objective of evaluating the effect of initial environment and substratum compositions in the survival, rooting and development of minicuttings of erva-mate. Shoots had been collected of ministumps produced for seed and cultivated in minigarden in semi-hydroponic system. The work was conducted in the delineation blocks in the bifactorial arrangement, with six substratum compositions: S1 - substratum for rooting with base of rind of Pinus, S2 - substratum for rooting with base of rind of Pinus and vermiculite, S3 - carbonized rind of rice + fine vermiculite + substratum for rooting with base of rind of Pinus and vermiculite (1:1:1 v/v), S4 - carbonized rind of rice + substratum for rooting with base of rind of Pinus and vermiculite (1:1 v/v), S5 - carbonized rind of rice + fine vermiculite (1:1 v/v) and S6 - coconut fiber and, two environments of rooting: automatized greenhouse and simple greenhouse. The results indicated that independent of the analyzed variable, the greenhouse with control oh humidity and temperature was superior to the environment without control and that the substratum formed by the mixture of carbonized rind of rice + substratum for rooting with base of rind of Pinus and vermiculite (1:1 v/v) is advised to be used in two environments for the rooting of juvenile minicuttings of erva-mate.